VReedom: training for authorized leave of absence through virtual reality – a feasibility study - Hendriks, Cylia; Jansen, Jochem Milan; Smit, Merel; Smulders, Lisanne M.; Popma, Arne; Van Der Pol, Thimo (Frontiers in Psychology, 2023)
This study assessed the feasibility, implementation process and outcomes of the VReedom training; a virtual reality (VR)-based intervention designed to prepare forensic psychiatric patients for their first authorized leave. Clinical forensic mental healthcare organization Inforsa, operating at security level 3, introduced the VReedom training for forensic patients eligible for their first authorized leave, between March 1st and November 13th, 2022. Employing a retrospective observational cohort study design with patient dossier data as the primary source, the study also used participant observation, weekly evaluative questionnaires and focus group discussions as data sources. Five objectives were utilized to evaluate the feasibility: recruitment capacity and resulting sample characteristics, data collection and evaluation procedures, acceptability and suitability of the training and protocol, training management and implementation, and preliminary participant results. Despite the lack of a control group, findings align with literature suggesting VR's potential for enhancing treatment motivation and reducing stress in preparation for first authorized leave. Of 13 patients approached, 10 participated without dropouts, and no incidents occurred during training. Emotion elicitation was successful, supporting VR Exposure therapy's efficacy. Findings align with literature, emphasizing VR's value in forensic psychiatry. Establishing favorable implementation conditions was crucial, with positive reception from treatment providers. Also, the need for personalization and additional locations was identified, and the training seemed most suitable for patients with a tbs-measure. Future research with control groups is recommended to further validate the effectiveness of the VReedom training intervention, and further protocol development is necessary to make it suitable for a broader population. Current findings contribute to the refinement and expansion of evidence-based practices in the field of VR-assisted training and treatment in forensic psychiatry.